TEST ANXIETY AND SELF CONCEPT AS PREDICTORS OF SECONDARY SCHOOL STUDENTS ACADEMIC ACHIEVEMENT IN BIOLOGY IN NNEWI EDUCATION ZONE OF ANAMBRA STATE, NIGERIA - Prof. Nneka Rita Nnorom; Nwanaka Austine Ekene (Adisam Publisher, 2025)
This study was carried out to determine the relationship between Test anxiety and Self- concept as predictor of secondary school students’ achievement in Biology in Nnewi Education Zone of Anambra State, Nigeria. Three research questions and three null hypotheses guided the study. The study was correlational research design with a population of 2,229, and sample size of 339 senior secondary three students (SSSIII) respectively. The sample size was obtained based on Taro Yamane principle and distributed using the proportionate stratified sampling technique. The instruments for data collection were Biology Achievement Test (BAT), Biology Text Anxiety Scale (BTAS) and Self-Descriptive Questionnaire (SDQ). The BTAS and SDQ were based on a Four-point Likert format and were used to gather data on students’ Test-anxiety and Self-concept. Student Academic Achievement Scores (SAA) were obtained from the teacher made test. The BTAS and SDQ were validated by three experts, one from Measurement and Evaluation Department, two from Science Education Department, and both from Chukwuemeka Odumegwu Ojukwu University. The reliability co-efficient of 0.73 and 0.74 were established using Cronbach Alpha for BTAS and SDQ respectively, while that of the BAT, was done using Kuder Richardson 20 (K-R-20) to obtain a reliability index of 0.775. Research questions and hypotheses were analyzed using simple and multiple regression analyses tested at 0.05 level of significance. Findings showed that Test-anxiety has a significant prediction on academic achievement of senior secondary school students in biology; Self-concept has a significant prediction on achievement of senior secondary school students in biology; test-anxiety has significantly predicted the academic achievement of male and female senior secondary school students in biology class; Self-concept significantly predicted the achievement of male and female senior secondary school students in biology class; and test-anxiety and self-concept had a joint and significant predictive power on achievement of senior secondary school students in biology in Nnewi Education Zone of Anambra State. Based on the findings of the study, educational implications were discussed. Recommendations included that Biology teachers be trained on how to improve and sustain students’ Test Anxiety and Self Concept in Biology. The study contributed to knowledge in that it revealed the nexus between test-anxiety and self-concept on students learning outcomes by showing that test anxiety (TA) and self-concept (SC) are psychological constructs that secondary school teachers in their respective discipline must critically pay attention to especially as it concerns biology in Nnewi Education Zone of Anambra State.